2012
DOI: 10.1109/tps.2012.2214063
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of the Multipactor Threshold Due to Electron Cyclotron Resonance

Abstract: Single surface multipactor on metal surfaces is studied in the case when the microwave electric field is superimposed on a dc electric and a permanent magnetic field. Based on a simple analysis of the electron motion it is predicted that considerable reduction in the multipactor threshold is possible when the electron cyclotron frequency equals the microwave field frequency and the permanent magnetic field has the proper orientation with respect to the metal surface. The prediction is confirmed by numerical si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 27 publications
1
7
0
Order By: Relevance
“…2 that there is a frequency gap interval (for both H 0 = 500 Oe and H 0 = 1000 Oe situations) where the multipactor voltage threshold is even less than for the nonmagnetized ferrite case. These results are consistent with [14] and [31], wherein it is experimentally demonstrated that the presence of an external DC magnetic field may lead to an enhancement of the multipacting effect for certain values of the external static magnetic field strength.…”
Section: Simulationssupporting
confidence: 90%
See 2 more Smart Citations
“…2 that there is a frequency gap interval (for both H 0 = 500 Oe and H 0 = 1000 Oe situations) where the multipactor voltage threshold is even less than for the nonmagnetized ferrite case. These results are consistent with [14] and [31], wherein it is experimentally demonstrated that the presence of an external DC magnetic field may lead to an enhancement of the multipacting effect for certain values of the external static magnetic field strength.…”
Section: Simulationssupporting
confidence: 90%
“…This fact destroys the electron resonant trajectories, forcing many low energetic impacts in which the electron is not favored by the RF electric field polarity, and it is pushed back to the departure wall. Both the electron orbit radius and the orbital velocity due to the external DC magnetic field depend on the magnetic field strength, the amplitude of the RF voltage, the ratio between the cyclotron frequency (f c = (eµ 0 H 0 )/(2πm)) and the frequency of the RF electromagnetic field [14]. Thus, when the radius of this circular motion is shorter than the waveguide gap value d, the electron will not be able to reach the opposite conductor, as it happens with point A1.…”
Section: Simulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the external magnetic field influences the electron flight time between successive impacts with the coaxial walls. In the numerical simulations, it has been found that the ratio between the cyclotron frequency f c = (eB DC )/(2π m), and the frequency of the RF electromagnetic field, plays a crucial role in the multipactor behavior, as reported in [4]. Fig.…”
Section: A Uniform Static Axial Magnetic Fieldmentioning
confidence: 78%
“…The basic physics involved in the multipactor phenomenon is well known for the case of a homogeneous rf field between two infinite parallel plates. However, most realistic rf device such as circulators and isolators involve inhomogeneous rf electric fields, complex material such as ferrites and the use of permanent magnetic field [1] [2]. In such situations, the evaluation of the Multipactor risks can be complicated as no prediction means were set-up.…”
Section: Introductionmentioning
confidence: 99%